Pulmonary Resection in Complicated Primary Pediatric Pulmonary Tuberculosis: An Evidence-based Case Report - Wibowo, Hendra; Wardoyo, Suprayitno; Shinta, Dhama (UI Scholars Hub, 2019)
Introduction. Paediatric pulmonary tuberculosis incidence was increasing, with many undetected cases. Antituberculosis regiments are known to be the treatment of choice for tuberculosis. Even though pulmonary resection for pulmonary tuberculosis has reduced in daily practice, it remains continues to play an important role in several advanced conditions and complications. Currently, there are no specific practical guidelines concerning surgical indications and approaches for pulmonary tuberculosis. We report a case with complicated primary paediatric pulmonary tuberculosis underwent resection and looking for the literature of the best evidence. Method. A case report completed with a discussion based on the best evidence. The database used for the literature search were Cochrane, Medline, ProQuest, and ScienceDirect. Keywords for the search were “primary pulmonary tuberculosis”, “surgery”, “Lung resection”, and “children”. Inclusion criteria were studies in English, children under 18 years old as the subject, and full-text articles available. The assessment carried out according to Oxford Centre for Evidence-Based Medicine 2011. Results. Six cohort studies were analyzed. Surgery indicated for patients with complicated TB that were unresponsive towards treatment. It should be noted that the experiments were done before the standard WHO antituberculosis therapy was applied. Thus, the result may be different from the current application. Conclusion. Currently, there was no guideline on pulmonary resection. However, surgery yielded better mortality and morbidity in children with complicated pulmonary tuberculosis.